Consumers preferences towards meat and meat products with traceability systems in Klang Valley, Malaysia - Basri, Hani Nabila; Mohd Nawi, Nolila; Kamarulzaman, Nitty Hirawaty; Shamsudin, Mad Nasir (International Organization Of Scientific Research, 2017)
Nowadays, consumers’ concerns towards food safety have significantly increasing and they tend to generally aware about their health. This concern has become particularly serious because of food scandal and countless cases that happened around the world. These scandals lead to negative effect and perception to consumers, food companies and also both supply and demand chain. There are a lot of strategies by agriculture food industries to increase food safety such as developed and implemented traceability systems among consumers. However, the awareness level towards traceability system among Malaysian consumers was low. The aim of this research is to determine consumers’ preferences towards meat and meat products with traceability systems in Klang Valley, Malaysia. This study was based on a quantitative approach and the primary data were collected using structured questionnaire via face to face interview with 503 respondents. Data collected were analyzed using descriptive analysis and chi square analysis. The results of the study indicated that majority of the consumers prefer to use traceability systems and they think traceability systems are important when buying meat and meat products. In addition, the results of chi-square analysis revealed that socio-demographics profile such as gender, race, marital status, educational level, income and household size has an association with respondent’s preferences towards meat and meat products with traceability systems. Traceability systems have the potential to be implemented if the government, meat producers, marketers, and retailers have a better understanding towards preference of consumers towards meat and meat products with traceability systems .It also allows them to start planning for the implementation of traceability system in near future as a strategy to improve their service which in line with the increasing of food safety awareness among consumers.